High-temperature-resistant boron nitride coating for electrical insulation and preparation method of high-temperature-resistant boron nitride coating
By combining large- and small-particle-size boron nitride, boron oxide, mullite sol, and other raw materials, the prepared boron nitride coating exhibits strong adhesion and good high-temperature resistance on the surface of graphite parts. This solves the problems of poor adhesion and insufficient temperature resistance of existing coatings, achieving the effect of low-temperature bonding and non-detachment at high temperatures.
Patent Information
- Application Number
- CN202510776682.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-11-04
AI Technical Summary
Existing boron nitride coatings have poor adhesion to graphite surfaces, poor high-temperature resistance, and complex preparation methods, use of toxic gases, high equipment costs, and high bonding temperatures.
A high-temperature resistant boron nitride coating for electrical insulation was prepared by ball milling and sieving using a combination of large and small particle sizes of boron nitride, boron oxide, mullite sol, organic additives, wetting agents, dispersants and defoamers. The mullite sol was used to bond at low temperatures and form a bridging effect at high temperatures, thereby improving adhesion.
It maintains excellent adhesion at high temperatures, has a low bonding temperature, and the coating does not peel off at high temperatures, exhibiting excellent adhesion and meeting the requirements for high-temperature electrical insulation.
Smart Images

Figure CN120888199A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high-temperature-resistant coatings, in particular to a boron nitride coating for high-temperature-resistant electrical insulation and a preparation method thereof. BACKGROUND
[0002] Graphite is often used as a heating body or a bearing element in a high-temperature vacuum furnace as a refractory, heat-insulating and high-temperature-resistant material. Graphite workpieces are usually formed by extrusion or isostatic pressing, and then are processed into fixed shapes and sizes. Due to the properties of graphite, graphite in a high-temperature furnace is easy to volatilize at a high temperature greater than 1800 DEG C, which can cause pollution of sintered products. Hexagonal boron nitride having a structure similar to that of graphite has better chemical stability in a high-temperature inert atmosphere. Therefore, if a boron nitride layer is coated on the surface of a graphite workpiece, the boron nitride layer can not only have an insulating effect, but also effectively prevent the volatilization of carbon elements, prevent the pollution of sintered products, and delay the oxidation and aging rate of the graphite workpiece, thereby prolonging the service life of the graphite workpiece.
[0003] In the prior art, boron chloride or boron bromide is usually used as a boron source to prepare a boron nitride coating by chemical vapor deposition in a mixed atmosphere of ammonia and nitrogen to deposit a pyrolytic boron nitride coating on the surface of a graphite workpiece. However, the inventors have found that the reaction raw material ammonia is a toxic gas with a pungent odor, and is easy to burn when mixed with air, which is not conducive to environmental protection and production safety. In addition, the reaction product contains hydrogen halide acid, which puts higher requirements on the salt acid corrosion resistance of the equipment, resulting in higher costs of equipment purchase and maintenance.
[0004] In addition, there is a boron nitride coating on the market, which can be sprayed or brushed on the surface of a graphite workpiece. However, the commercially available boron nitride coating generally has poor adhesion and poor high-temperature resistance. For example, Chinese patent CN108585634A discloses a boron nitride high-temperature-resistant anticorrosive coating and a preparation method thereof. Although the boron nitride anticorrosive coating disclosed in the patent has good corrosion resistance, it has poor heat resistance.
[0005] In addition, although many patents related to boron nitride coating disclose how to prepare boron nitride coating, the preparation method is complicated and has a high bonding temperature. For example, Chinese patent CN107201066B discloses an anti-sticking aluminum coating, but it needs to be dried at 700-720 DEG C after brushing and then can be used; Chinese patent CN103708843A discloses a boron nitride coating and a use method, but the boron nitride coating needs to be heated to 1600 DEG C under nitrogen protection for use. SUMMARY
[0006] In view of the deficiencies of the prior art, the present application provides a boron nitride coating for high-temperature-resistant electric insulation and a preparation method thereof, the boron nitride coating has excellent adhesion and high-temperature resistance, and has low bonding temperature.
[0007] To solve the above technical problems, the technical scheme adopted by the present application is as follows: A boron nitride coating for high-temperature-resistant electric insulation comprises the following raw materials by weight: 10-12 parts of large-particle-size boron nitride, 10-13 parts of small-particle-size boron nitride, 1.5-2 parts of boron oxide, 16-20 parts of mullite sol, 65-75 parts of water, 7-8 parts of organic additive, 0.3-0.4 parts of wetting agent, 3.5-4.5 parts of dispersant, and 0.4-0.5 parts of defoaming agent.
[0008] The particle size of the large-particle-size boron nitride is 20-50 microns.
[0009] The particle size of the small-particle-size boron nitride is 2-4 microns.
[0010] The particle size of the boron oxide is 200 microns.
[0011] The preparation method of the mullite sol comprises the following steps: preparing an aluminum nitrate solution, preparing a mixed polyvinyl alcohol solution, preparing a first mullite sol, preparing a second mullite sol, and mixing. In the preparation of the aluminum nitrate solution, the treated aluminum nitrate is mixed with anhydrous ethanol, and then stirred at 55-70 DEG C until dissolved to obtain the aluminum nitrate solution. In the preparation of the aluminum nitrate solution, the mass ratio of the treated aluminum nitrate to anhydrous ethanol is 1:10-15. In the preparation of the mixed polyvinyl alcohol solution, the polyvinyl alcohol 1788 aqueous solution is mixed with Tween 80, and then stirred at room temperature for 25-30 minutes to obtain the mixed polyvinyl alcohol solution. The mass ratio of the polyvinyl alcohol 1788 aqueous solution to Tween 80 is 1000:2-3. The mass concentration of the polyvinyl alcohol 1788 aqueous solution is 10%. In the preparation of the first mullite sol, the aluminum nitrate solution is mixed with tetraethyl orthosilicate, and then stirred and refluxed at 60-70 DEG C for 10-15 minutes, the mixed polyvinyl alcohol solution is added, and then dilute nitric acid is slowly added to adjust the pH to 2.5, and then stirred and refluxed for 0.5-1 hour, the temperature is raised to 70-80 DEG C, and then stirred and refluxed for 0.5-1 hour, the temperature is raised to 100-110 DEG C, and then stirred and refluxed for 0.5 hour to obtain the first mullite sol. In the preparation of the first mullite sol, the molar ratio of aluminum nitrate in the aluminum nitrate solution to tetraethyl orthosilicate is 3-3.2:1. The mass ratio of the aluminum nitrate solution to the mixed polyvinyl alcohol solution is 100:4-5; The molar concentration of the dilute nitric acid is 0.1-0.2 mol / L; The adding speed of the dilute nitric acid is 3-5 mL / min; In the preparation of the second portion of the mullite sol, the tetraethyl orthosilicate and the anhydrous ethanol are mixed, stirred at room temperature for 20-30 min, the aluminum isopropoxide is added, stirred for 30-40 min, stirred and refluxed at 60-70 DEG C for 1.5-2 h, cooled to 25-30 DEG C, the aluminum nitrate solution is added, stirred and refluxed for 10-11 h, heated to 50-60 DEG C, stirred and refluxed for 3-4 h, heated to 80-90 DEG C, stirred and refluxed for 10-11 h, to obtain the second portion of the mullite sol; In the preparation of the second portion of the mullite sol, the mass ratio of the tetraethyl orthosilicate to the anhydrous ethanol is 13-15:50-55; The molar ratio of the tetraethyl orthosilicate to the aluminum isopropoxide is 1:2.6-2.8; The molar ratio of the aluminum isopropoxide to the aluminum nitrate in the aluminum nitrate solution is 5.7-6:1; In the mixing, after the first portion of the mullite sol and the second portion of the mullite sol are mixed, uniform stirring is performed, and then vacuum concentration is performed until the solid content is 27-32%, to obtain the mullite sol; In the mixing, the mass ratio of the first portion of the mullite sol to the second portion of the mullite sol is 10:2-2.4; The temperature of the vacuum concentration is 60-70 DEG C, and the vacuum degree is 0.02-0.05 MPa.
[0012] The organic auxiliary agent is one or a combination of hydroxyethyl cellulose and carboxymethyl cellulose.
[0013] The wetting agent is aqueous silicone oil.
[0014] The dispersing agent is a maleic acid-acrylic acid copolymer.
[0015] The defoaming agent is a polyether-modified organosilicon defoaming agent.
[0016] A preparation method of the foregoing high-temperature-resistant boron nitride coating for electrical insulation, comprising: preparing raw materials, and ball milling; In the preparation of the raw materials, the raw materials are weighed according to the specified weight fraction.
[0017] In the ball milling, the raw materials are mixed, uniformly stirred, and then subjected to ball milling and sieving, to obtain the high-temperature-resistant boron nitride coating for electrical insulation and the like; In the ball milling, the ball milling speed is 200-400 rpm, and the ball milling time is 1-4 h; In the sieving, a sieve with a mesh size of 200 meshes is used.
[0018] Compared with the prior art, the application has the following beneficial effects: (1) The boron nitride coating for high-temperature-resistant electric insulation of the application adds mullite sol and boron oxide. The mullite sol can act as a binder at low temperatures (below 500 DEG C) and can improve the adhesion of the boron nitride coating on graphite. As the temperature further rises to more than 500 DEG C, the organic substances in the mullite sol that act as binders are carbonized or oxidized and volatilized, and at this time, the boron oxide in the coating softens or even melts, which can also improve the adhesion of the coating. As the use temperature further rises to more than 900 DEG C, the viscosity of the boron oxide in the coating becomes smaller, and the mullite sol changes into a mullite microcrystalline structure. The needle-like mullite grains act as a bridge between the graphite and the boron nitride and between the boron nitride particles, which can also improve the adhesion of the coating. In addition, as the temperature further rises (more than 1800 DEG C), the mullite will partially decompose to form aluminum oxide and free silicon oxide at high temperatures, which can greatly promote the adhesion strength and thermal shock resistance of the coating after high-temperature treatment. Therefore, the boron nitride coating for high-temperature-resistant electric insulation of the application still has excellent adhesion after high-temperature treatment. (2) The boron nitride coating for high-temperature-resistant electric insulation of the application uses a mixture of a first mullite sol and a second mullite sol. The first mullite sol is prepared by a rapid heating method, which can obtain relatively large particle size mullite sol. The second mullite sol uses two aluminum sources, aluminum isopropoxide and aluminum nitrate, which is conducive to the formation of Al-O-Si bonds, and a gradual slow heating method is adopted to control the hydrolysis rate, so that relatively small particle size mullite sol can be obtained. After mixing the relatively large particle size mullite sol and the relatively small particle size mullite sol, the mullite sols of different particle sizes can form a dense coating. The relatively large particle size mullite sol can act as a skeleton, and during high-temperature treatment, the relatively small particle size mullite sol can preferentially decompose and absorb heat to avoid damaging the skeleton formed by the relatively large particle size mullite sol. Moreover, the relatively small particle size mullite sol can increase the contact area between the coating and the graphite, further improving the adhesion of the boron nitride coating for high-temperature-resistant electric insulation.
[0019] (3) The boron nitride coating for high-temperature-resistant electric insulation of the application has a low bonding temperature. The coating can be cured at 25 DEG C for 30 min. (4) The boron nitride coating for high-temperature-resistant electric insulation of the application has excellent adhesion. According to the GB / T 1720-2020 paint film circle test method, the adhesion of the coating is level 1. (5) The boron nitride coating for high-temperature-resistant electric insulation has excellent high-temperature resistance. After the boron nitride coating for high-temperature-resistant electric insulation is sprayed on the surface of a graphite sample and solidified, the graphite sample is placed at 1900 DEG C for 4 hours, and no coating peeling problem occurs on the surface of the graphite sample. After the boron nitride coating for high-temperature-resistant electric insulation is sprayed on the surface of a graphite sample and solidified, the graphite sample is placed at 1800 DEG C for 4 hours, and the paint adhesion is grade 2 according to the paint film circle test method of GB / T 1720-2020. After the boron nitride coating for high-temperature-resistant electric insulation is sprayed on the surface of a graphite sample and solidified, the graphite sample is placed at 1900 DEG C for 4 hours, and the paint adhesion is grade 2 according to the paint film circle test method of GB / T 1720-2020. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 The photos of the graphite samples 1-3 after the standing treatment in performance test 2. DETAILED DESCRIPTION
[0021] In order to have a clearer understanding of the technical features, objectives and effects of the present application, the specific embodiments of the present application will be described below.
[0022] Example 1 A boron nitride coating for high-temperature-resistant electric insulation comprises the following raw materials by weight: 10 parts of large-particle-size boron nitride, 10 parts of small-particle-size boron nitride, 1.5 parts of boron oxide, 16 parts of mullite sol, 65 parts of water, 7 parts of organic additive, 0.3 parts of wetting agent, 3.5 parts of dispersing agent, and 0.4 parts of defoaming agent.
[0023] The particle size of the large-particle-size boron nitride is 20 microns.
[0024] The particle size of the small-particle-size boron nitride is 2 microns.
[0025] The particle size of the boron oxide is 200 microns.
[0026] The preparation method of the mullite sol is as follows: 1. Prepare an aluminum nitrate solution: treat aluminum nitrate nonahydrate at normal pressure and at a temperature of 80 DEG C until a constant weight is obtained, to obtain treated aluminum nitrate, mix the treated aluminum nitrate with anhydrous ethanol, and stir at 55 DEG C until dissolution, to obtain an aluminum nitrate solution; The mass ratio of the treated aluminum nitrate to anhydrous ethanol is 1:10; 2. Prepare a mixed polyvinyl alcohol solution: mix a polyvinyl alcohol 1788 aqueous solution with Tween 80, and stir at room temperature for 25 minutes, to obtain a mixed polyvinyl alcohol solution; The mass ratio of the polyvinyl alcohol 1788 aqueous solution to Tween 80 is 1000:2; The mass concentration of the polyvinyl alcohol 1788 aqueous solution is 10%. 3. Preparation of the first portion of mullite sol: After mixing the aluminum nitrate solution with tetraethyl orthosilicate, stirring and refluxing at 60℃ for 10 min, adding a mixed polyvinyl alcohol solution, then slowly adding dilute nitric acid to adjust the pH to 2.5, stirring and refluxing for 0.5 h, increasing the temperature to 70℃, stirring and refluxing for 0.5 h, increasing the temperature to 100℃, stirring and refluxing for 0.5 h, to obtain the first portion of mullite sol; The molar ratio of aluminum nitrate in the aluminum nitrate solution to tetraethyl orthosilicate is 3:1; The mass ratio of the aluminum nitrate solution to the mixed polyvinyl alcohol solution is 100:4; The molar concentration of the dilute nitric acid is 0.1 mol / L; The addition speed of the dilute nitric acid is 3 mL / min; 4. Preparation of the second portion of mullite sol: After mixing the tetraethyl orthosilicate with anhydrous ethanol, stirring at room temperature for 20 min, adding aluminum isopropoxide, stirring for 30 min, stirring and refluxing at 60℃ for 1.5 h, reducing the temperature to 25℃, adding the aluminum nitrate solution, stirring and refluxing for 10 h, increasing the temperature to 50℃, stirring and refluxing for 3 h, increasing the temperature to 80℃, stirring and refluxing for 10 h, to obtain the second portion of mullite sol; The mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 13:50; The molar ratio of tetraethyl orthosilicate to aluminum isopropoxide is 1:2.6; The molar ratio of aluminum isopropoxide to aluminum nitrate in the aluminum nitrate solution is 5.7:1; 5. Mixing: After mixing the first portion of mullite sol with the second portion of mullite sol, stirring uniformly, then vacuum concentration at a temperature of 60℃ and a vacuum degree of 0.02 MPa to a solid content of 27%, to obtain the mullite sol; The mass ratio of the first portion of mullite sol to the second portion of mullite sol is 10:2.
[0027] The organic auxiliary agent is hydroxyethyl cellulose.
[0028] The wetting agent is aqueous silicone oil.
[0029] The dispersing agent is maleic acid-acrylic acid copolymer.
[0030] The defoaming agent is polyether-modified silicone defoaming agent.
[0031] The embodiment also provides a preparation method of the aforementioned high-temperature-resistant boron nitride coating for electrical insulation, specifically: 1. Preparation of raw materials: The raw materials are weighed according to the specified weight fraction.
[0032] 2. Ball milling: After mixing and stirring the raw materials uniformly, ball milling and sieving are performed to obtain the high-temperature-resistant boron nitride coating for electrical insulation and the like; The ball milling rotation speed in the ball milling is 200 rpm, and the ball milling time is 1 h. The mesh number of the screen used in the sieving is 200 mesh.
[0033] Embodiment 2 A high-temperature-resistant boron nitride coating for electrical insulation comprises the following raw materials by weight: 11 parts of large-particle-size boron nitride, 12 parts of small-particle-size boron nitride, 1.8 parts of boron oxide, 18 parts of mullite sol, 70 parts of water, 7.5 parts of organic additive, 0.3 parts of wetting agent, 4 parts of dispersing agent, and 0.5 parts of defoaming agent.
[0034] The particle size of the large-particle-size boron nitride is 30 μm.
[0035] The particle size of the small-particle-size boron nitride is 3 μm.
[0036] The particle size of the boron oxide is 200 μm.
[0037] The preparation method of the mullite sol is as follows: 1. Preparing an aluminum nitrate solution: treating aluminum nitrate nonahydrate under normal pressure and at a temperature of 85°C until a constant weight is obtained to obtain treated aluminum nitrate, mixing the treated aluminum nitrate with anhydrous ethanol, and stirring at 65°C until dissolution to obtain an aluminum nitrate solution; The mass ratio of the treated aluminum nitrate to the anhydrous ethanol is 1:12; 2. Preparing a mixed polyvinyl alcohol solution: mixing a polyvinyl alcohol 1788 aqueous solution with Tween 80, and stirring at room temperature for 30 min to obtain a mixed polyvinyl alcohol solution; The mass ratio of the polyvinyl alcohol 1788 aqueous solution to Tween 80 is 1000:2.5; The mass concentration of the polyvinyl alcohol 1788 aqueous solution is 10%; 3. Preparing a first mullite sol: mixing the aluminum nitrate solution with tetraethyl orthosilicate, stirring and refluxing at 65°C for 12 min, adding the mixed polyvinyl alcohol solution, then slowly adding dilute nitric acid to adjust the pH to 2.5, stirring and refluxing for 0.5 h, increasing the temperature to 75°C, stirring and refluxing for 1 h, increasing the temperature to 105°C, and stirring and refluxing for 0.5 h to obtain a first mullite sol; The molar ratio of aluminum nitrate in the aluminum nitrate solution to tetraethyl orthosilicate is 3.1:1; The mass ratio of the aluminum nitrate solution to the mixed polyvinyl alcohol solution is 100:4.5; The molar concentration of the dilute nitric acid is 0.2 mol / L; The addition speed of the dilute nitric acid is 4 mL / min; 4. Preparation of the second portion of mullite sol: after mixing the tetraethyl orthosilicate and anhydrous ethanol, stirring at room temperature for 25 min, adding aluminum isopropoxide, stirring for 35 min, stirring and refluxing at 65 DEG C for 2 h, cooling to 25 DEG C, adding aluminum nitrate solution, stirring and refluxing for 10.5 h, heating to 55 DEG C, stirring and refluxing for 3.5 h, heating to 85 DEG C, stirring and refluxing for 10.5 h, to obtain the second portion of mullite sol; The mass ratio of the tetraethyl orthosilicate to the anhydrous ethanol is 14:53; The molar ratio of the tetraethyl orthosilicate to the aluminum isopropoxide is 1:2.7; The molar ratio of the aluminum isopropoxide to the aluminum nitrate in the aluminum nitrate solution is 5.8:1; 5. Mixing: after mixing the first portion of mullite sol and the second portion of mullite sol, stirring uniformly, then vacuum concentration at a temperature of 65 DEG C and a vacuum degree of 0.04 MPa to a solid content of 30%, to obtain the mullite sol; The mass ratio of the first portion of mullite sol to the second portion of mullite sol is 10:2.2.
[0038] The organic auxiliary agent is carboxymethyl cellulose.
[0039] The wetting agent is aqueous silicone oil.
[0040] The dispersing agent is maleic acid-acrylic acid copolymer.
[0041] The defoaming agent is polyether-modified organosilicon defoaming agent.
[0042] The embodiment also provides a preparation method of the aforementioned high-temperature-resistant boron nitride coating for electrical insulation, specifically: 1. Preparation of raw materials: according to the specified weight parts, each raw material is weighed.
[0043] 2. Ball milling: after mixing and stirring each raw material uniformly, ball milling and sieving are performed, to obtain the high-temperature-resistant boron nitride coating for electrical insulation and the like; The ball milling speed in the ball milling is 300 rpm, and the ball milling time is 3 h. The mesh number of the sieve screen used in the sieving is 200 mesh.
[0044] Embodiment 3 A high-temperature-resistant boron nitride coating for electrical insulation comprises the following raw materials in weight parts: 12 parts of large-particle-size boron nitride, 13 parts of small-particle-size boron nitride, 2 parts of boron oxide, 20 parts of mullite sol, 75 parts of water, 8 parts of organic auxiliary agent, 0.4 parts of wetting agent, 4.5 parts of dispersing agent, and 0.5 parts of defoaming agent.
[0045] The particle size of the large-particle-size boron nitride is 50 μm.
[0046] The particle size of the small-particle-size boron nitride is 4 μm.
[0047] The particle size of the boron oxide is 200 μm.
[0048] The preparation method of the mullite sol is: 1. Preparation of aluminum nitrate solution: The aluminum nitrate nine hydrate is treated under normal pressure and at a temperature of 90℃ until a constant weight is obtained, to obtain treated aluminum nitrate. The treated aluminum nitrate is mixed with anhydrous ethanol and stirred at 70℃ until dissolved, to obtain an aluminum nitrate solution; The mass ratio of the treated aluminum nitrate to anhydrous ethanol is 1:15; 2. Preparation of mixed polyvinyl alcohol solution: The polyvinyl alcohol 1788 aqueous solution is mixed with Tween 80 and stirred at room temperature for 30 min, to obtain a mixed polyvinyl alcohol solution; The mass ratio of the polyvinyl alcohol 1788 aqueous solution to Tween 80 is 1000:3; The mass concentration of the polyvinyl alcohol 1788 aqueous solution is 10%; 3. Preparation of the first mullite sol: The aluminum nitrate solution is mixed with tetraethyl orthosilicate and stirred at 70℃ for 15 min, the mixed polyvinyl alcohol solution is added, then dilute nitric acid is slowly added to adjust the pH to 2.5, and stirred for 1 h, the temperature is raised to 80℃, and stirred for 1 h, the temperature is raised to 110℃, and stirred for 0.5 h, to obtain the first mullite sol; The molar ratio of aluminum nitrate in the aluminum nitrate solution to tetraethyl orthosilicate is 3.2:1; The mass ratio of the aluminum nitrate solution to the mixed polyvinyl alcohol solution is 100:5; The molar concentration of the dilute nitric acid is 0.2 mol / L; The addition speed of the dilute nitric acid is 5 mL / min; 4. Preparation of the second mullite sol: The tetraethyl orthosilicate is mixed with anhydrous ethanol and stirred at room temperature for 30 min, aluminum isopropoxide is added, and stirred for 40 min, the temperature is raised to 70℃, and stirred for 2 h, the temperature is lowered to 30℃, the aluminum nitrate solution is added, and stirred for 11 h, the temperature is raised to 60℃, and stirred for 4 h, the temperature is raised to 90℃, and stirred for 11 h, to obtain the second mullite sol; The mass ratio of the tetraethyl orthosilicate to anhydrous ethanol is 15:55; The molar ratio of the tetraethyl orthosilicate to aluminum isopropoxide is 1:2.8; The molar ratio of the aluminum isopropoxide to aluminum nitrate in the aluminum nitrate solution is 6:1; 5. Mixing: The first mullite sol is mixed with the second mullite sol, and stirred uniformly, then vacuum concentration is carried out at a temperature of 70℃ and a vacuum degree of 0.05 MPa until the solid content is 32%, to obtain the mullite sol; The mass ratio of the first portion of mullite sol to the second portion of mullite sol is 10:2.4.
[0049] The organic auxiliary agent is a combination of hydroxyethyl cellulose and carboxymethyl cellulose, wherein the mass ratio of hydroxyethyl cellulose to carboxymethyl cellulose is 1:1.
[0050] The wetting agent is aqueous silicone oil.
[0051] The dispersing agent is a maleic acid-acrylic acid copolymer.
[0052] The defoaming agent is a polyether-modified organosilicon defoaming agent.
[0053] The embodiment also provides a preparation method of the aforementioned high-temperature-resistant boron nitride coating for electrical insulation, and specifically comprises the following steps: 1. Preparing raw materials: taking each raw material according to the specified weight fraction.
[0054] 2. Ball milling: after mixing and uniformly stirring each raw material, ball milling and sieving are performed to obtain the high-temperature-resistant boron nitride coating for electrical insulation and the like. The ball milling speed in the ball milling is 400 rpm, and the ball milling time is 4 h. The mesh number of the sieve screen used in the sieving is 200 mesh.
[0055] Comparative Example 1 A high-temperature-resistant boron nitride coating for electrical insulation comprises the following raw materials in parts by weight: 10 parts of large-particle-size boron nitride, 10 parts of small-particle-size boron nitride, 1.5 parts of boron oxide, 16 parts of mullite sol, 65 parts of water, 7 parts of organic auxiliary agent, 0.3 parts of wetting agent, 3.5 parts of dispersing agent, and 0.4 parts of defoaming agent.
[0056] The particle size of the large-particle-size boron nitride is 20 µm.
[0057] The particle size of the small-particle-size boron nitride is 2 µm.
[0058] The particle size of the boron oxide is 200 µm.
[0059] The preparation method of the mullite sol is as follows: 1. Preparing an aluminum nitrate solution: treating aluminum nitrate nonahydrate under normal pressure and at a temperature of 80 ℃ until a constant weight is obtained to obtain treated aluminum nitrate, and then mixing the treated aluminum nitrate with anhydrous ethanol and stirring at 55 ℃ until dissolution to obtain an aluminum nitrate solution. The mass ratio of the treated aluminum nitrate to the anhydrous ethanol is 1:10. 2. Preparing a mixed polyvinyl alcohol solution: mixing a polyvinyl alcohol 1788 aqueous solution with Tween 80 and stirring at room temperature for 25 min to obtain a mixed polyvinyl alcohol solution. The mass ratio of the polyvinyl alcohol 1788 aqueous solution to Tween 80 is 1000:2; The mass concentration of the polyvinyl alcohol 1788 aqueous solution is 10%. 3. Preparing the mullite sol: mixing the aluminum nitrate solution and the tetraethyl orthosilicate, stirring and refluxing at 60℃ for 10 min, adding the mixed polyvinyl alcohol solution, then slowly adding dilute nitric acid to adjust the pH to 2.5, stirring and refluxing for 0.5 h, increasing the temperature to 70℃, stirring and refluxing for 0.5 h, increasing the temperature to 100℃, stirring and refluxing for 0.5 h, to obtain the mullite sol; The molar ratio of aluminum nitrate to tetraethyl orthosilicate in the aluminum nitrate solution is 3:1. The mass ratio of the aluminum nitrate solution to the mixed polyvinyl alcohol solution is 100:4. The molar concentration of the dilute nitric acid is 0.1 mol / L. The adding speed of the dilute nitric acid is 3 mL / min.
[0060] The organic auxiliary agent is hydroxyethyl cellulose.
[0061] The wetting agent is aqueous silicone oil.
[0062] The dispersing agent is maleic acid-acrylic acid copolymer.
[0063] The defoaming agent is polyether-modified silicone defoaming agent.
[0064] The present comparative example also provides a preparation method of the aforementioned high-temperature-resistant boron nitride coating for electrical insulation, specifically: 1. Preparing raw materials: taking each raw material according to the specified weight fraction.
[0065] 2. Ball milling: mixing each raw material, stirring uniformly, then ball milling and sieving to obtain the high-temperature-resistant boron nitride coating for electrical insulation and the like. The ball milling speed in the ball milling is 200 rpm, and the ball milling time is 1 h. The mesh number of the sieve screen used in the sieving is 200 mesh.
[0066] Comparative Example 2 A high-temperature-resistant boron nitride coating for electrical insulation comprises the following raw materials in weight fractions: 10 parts of large-particle-size boron nitride, 10 parts of small-particle-size boron nitride, 1.5 parts of boron oxide, 16 parts of mullite sol, 65 parts of water, 7 parts of organic auxiliary agent, 0.3 parts of wetting agent, 3.5 parts of dispersing agent, and 0.4 parts of defoaming agent.
[0067] The particle size of the large-particle-size boron nitride is 20 μm.
[0068] The particle size of the small-particle-size boron nitride is 2 μm.
[0069] The particle size of the boron oxide is 200 μm.
[0070] The preparation method of the mullite sol is: 1. Prepare an aluminum nitrate solution: treat aluminum nitrate nonahydrate at normal pressure and a temperature of 80 DEG C until a constant weight is obtained to obtain treated aluminum nitrate, mix the treated aluminum nitrate with anhydrous ethanol, and stir at 55 DEG C until dissolved to obtain an aluminum nitrate solution; The mass ratio of the treated aluminum nitrate to the anhydrous ethanol is 1:10; 2. Prepare a mullite sol: mix tetraethyl orthosilicate with anhydrous ethanol, stir at room temperature for 20 min, add aluminum isopropoxide, stir for 30 min, stir and reflux at 60 DEG C for 1.5 h, cool to 25 DEG C, add the aluminum nitrate solution, stir and reflux for 10 h, warm to 50 DEG C, stir and reflux for 3 h, warm to 80 DEG C, and stir and reflux for 10 h to obtain a mullite sol; The mass ratio of the tetraethyl orthosilicate to the anhydrous ethanol is 13:50; The molar ratio of the tetraethyl orthosilicate to the aluminum isopropoxide is 1:2.6; The molar ratio of the aluminum isopropoxide to the aluminum nitrate in the aluminum nitrate solution is 5.7:1.
[0071] The organic additive is hydroxyethyl cellulose.
[0072] The wetting agent is aqueous silicone oil.
[0073] The dispersing agent is a maleic acid-acrylic acid copolymer.
[0074] The defoaming agent is a polyether-modified organosilicon defoaming agent.
[0075] The present comparative example also provides a preparation method of the aforementioned high-temperature-resistant boron nitride coating for electrical insulation, specifically: 1. Prepare raw materials: take each raw material according to the specified weight fraction.
[0076] 2. Ball mill: mix and uniformly stir each raw material, then ball mill and sieve to obtain a high-temperature-resistant boron nitride coating for electrical insulation and the like; The ball milling speed in the ball milling is 200 rpm, and the ball milling time is 1 h; The mesh number of the sieve used in the sieving is 200 mesh.
[0077] Comparative Example 3 A high-temperature-resistant boron nitride coating for electrical insulation comprises the following raw materials in weight fractions: 10 parts of large-particle-size boron nitride, 10 parts of small-particle-size boron nitride, 16 parts of mullite sol, 65 parts of water, 7 parts of organic additive, 0.3 parts of wetting agent, 3.5 parts of dispersing agent, and 0.4 parts of defoaming agent.
[0078] The particle size of the large-particle-size boron nitride is 20 mu m.
[0079] The particle size of the small-particle-size boron nitride is 2 pm.
[0080] The particle size of the boron oxide is 200 pm.
[0081] The preparation method of the mullite sol is: 1. preparing an aluminum nitrate solution: treating aluminum nitrate nonahydrate under normal pressure and at a temperature of 80°C until a constant weight is obtained, obtaining treated aluminum nitrate, mixing the treated aluminum nitrate with anhydrous ethanol, and stirring at 55°C until dissolution, to obtain an aluminum nitrate solution; The mass ratio of the treated aluminum nitrate to the anhydrous ethanol is 1:10; 2. preparing a mixed polyvinyl alcohol solution: mixing a polyvinyl alcohol 1788 aqueous solution with Tween 80, and stirring at room temperature for 25 min, to obtain a mixed polyvinyl alcohol solution; The mass ratio of the polyvinyl alcohol 1788 aqueous solution to Tween 80 is 1000:2; The mass concentration of the polyvinyl alcohol 1788 aqueous solution is 10%; 3. preparing a first mullite sol: mixing the aluminum nitrate solution with tetraethyl orthosilicate, stirring and refluxing at 60°C for 10 min, adding the mixed polyvinyl alcohol solution, then slowly adding dilute nitric acid to adjust the pH to 2.5, stirring and refluxing for 0.5 h, increasing the temperature to 70°C, stirring and refluxing for 0.5 h, increasing the temperature to 100°C, and stirring and refluxing for 0.5 h, to obtain a first mullite sol; The molar ratio of aluminum nitrate in the aluminum nitrate solution to tetraethyl orthosilicate is 3:1; The mass ratio of the aluminum nitrate solution to the mixed polyvinyl alcohol solution is 100:4; The molar concentration of the dilute nitric acid is 0.1 mol / L; The addition speed of the dilute nitric acid is 3 mL / min; 4. preparing a second mullite sol: mixing tetraethyl orthosilicate with anhydrous ethanol, stirring at room temperature for 20 min, adding aluminum isopropoxide, stirring for 30 min, stirring and refluxing at 60°C for 1.5 h, decreasing the temperature to 25°C, adding the aluminum nitrate solution, stirring and refluxing for 10 h, increasing the temperature to 50°C, stirring and refluxing for 3 h, increasing the temperature to 80°C, and stirring and refluxing for 10 h, to obtain a second mullite sol; The mass ratio of tetraethyl orthosilicate to anhydrous ethanol is 13:50; The molar ratio of tetraethyl orthosilicate to aluminum isopropoxide is 1:2.6; The molar ratio of aluminum isopropoxide to aluminum nitrate in the aluminum nitrate solution is 5.7:1; 5. Mixing: after mixing the first portion of mullite sol with the second portion of mullite sol, stirring uniformly, then vacuum concentration under the condition of temperature 60℃ and vacuum degree 0.02MPa to solid content 27%, obtaining mullite sol; The mass ratio of the first portion of mullite sol to the second portion of mullite sol is 10:2.
[0082] The organic auxiliary agent is hydroxyethyl cellulose.
[0083] The wetting agent is aqueous silicone oil.
[0084] The dispersing agent is maleic acid-acrylic acid copolymer.
[0085] The defoaming agent is polyether modified silicone defoaming agent.
[0086] The present comparative example also provides a preparation method of the aforementioned boron nitride coating for high-temperature-resistant and electrically-insulating purposes, specifically: 1. Preparing raw materials: taking each raw material according to the specified weight fraction.
[0087] 2. Ball milling: after mixing each raw material and stirring uniformly, then ball milling and sieving, obtaining boron nitride coating for high-temperature-resistant and electrically-insulating purposes; The ball milling speed in the ball milling is 200rpm, and the ball milling time is 1h; The mesh number of the sieve screen used in the sieving is 200mesh.
[0088] Performance test 1 The boron nitride coating for high-temperature-resistant and electrically-insulating purposes prepared by the examples 1-3 and the comparative examples 1-3 is sprayed on the surface of the graphite sample, then placed at 25℃ for 30min, observing whether solidification is achieved, and the observation results are shown in Table 1: Table 1
[0089] Performance test 2 Taking 3 graphite samples, numbered as No.1-3 graphite samples, No.1 graphite sample as control, without spraying coating, uniformly spraying the boron nitride coating for high-temperature-resistant and electrically-insulating purposes prepared by the example 1 on the surface of No.2 and No.3 graphite samples, then placing No.1-3 graphite samples at 25℃ for 30min to achieve coating solidification, then performing standing treatment on the solidified No.1-3 graphite samples, specifically, placing No.1 and No.2 graphite samples at room temperature for 4h, and placing No.3 graphite sample at 1900℃ for 4h, and the photos of the standing-treated No.1-3 graphite samples are shown in Figure 1 Compared with the standing-treated No.2 graphite sample, whether the standing-treated No.3 graphite sample has coating peeling problem on the surface, and through observation, the standing-treated No.3 graphite sample does not have coating peeling problem on the surface.
[0090] As can be seen from the structure of the performance test, the high-temperature-resistant boron nitride coating prepared in Example 1 does not have the problem of coating falling off after standing at 1900℃ for 4h.
[0091] Performance Test 3 The high-temperature-resistant boron nitride coatings prepared in Examples 1-3 and Comparative Examples 1-3 were sprayed on the surface of a graphite sample, then stood at 25℃ for 30min, and then the paint adhesion on the surface of the graphite sample was tested according to the GB / T 1720-2020 paint film circle test method. The test results are shown in Table 2: Table 2
[0092] As can be seen from the results of the performance test, the paint adhesion of the high-temperature-resistant boron nitride coating of Comparative Example 1 is lower than that of the high-temperature-resistant boron nitride coating of Example 1.
[0093] Performance Test 4 The high-temperature-resistant boron nitride coatings prepared in Examples 1-3 and Comparative Examples 1-3 were sprayed on the surface of a graphite sample, then stood at 25℃ for 30min, and then the paint adhesion on the surface of the graphite sample was tested according to the GB / T 1720-2020 paint film circle test method. The test results are shown in Table 3: Table 3
[0094] As can be seen from the results of the performance test, the paint adhesion of the high-temperature-resistant boron nitride coatings of Comparative Examples 1-3 decreases more than that of the high-temperature-resistant boron nitride coating of Example 1 after standing at 1800℃ for 4h.
[0095] Performance Test 5 The high-temperature-resistant boron nitride coatings prepared in Examples 1-3 and Comparative Examples 1-3 were sprayed on the surface of a graphite sample, then stood at 25℃ for 30min, and then the paint adhesion on the surface of the graphite sample was tested according to the GB / T 1720-2020 paint film circle test method. The test results are shown in Table 4: Table 4
[0096] As can be seen from the results of the performance test, the paint adhesion of the high-temperature-resistant boron nitride coatings of Comparative Examples 1-3 decreases more than that of the high-temperature-resistant boron nitride coating of Example 1 after standing at 1900℃ for 4h.
[0097] Unless otherwise indicated, percentages employed in the present application are by mass.
[0098] Finally, it should be noted that the above only represents the preferred embodiments of the present application and is not intended to limit the present application. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art will appreciate that modifications can be made to the technical solutions described in the foregoing embodiments, or some of the technical features thereof can be replaced equivalently, without departing from the spirit and principle of the present application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.
Claims
1. A boron nitride coating for high temperature electrical insulation, characterized in that, The raw materials include the following components by weight: 10-12 parts of large-size boron nitride, 10-13 parts of small-size boron nitride, 1.5-2 parts of boron oxide, 16-20 parts of mullite sol, 65-75 parts of water, 7-8 parts of organic additives, 0.3-0.4 parts of wetting agent, 3.5-4.5 parts of dispersing agent, and 0.4-0.5 parts of defoaming agent; The preparation method of the mullite sol comprises the following steps: preparing an aluminum nitrate solution, preparing a mixed polyvinyl alcohol solution, preparing a first mullite sol, preparing a second mullite sol, and mixing; In the preparation of the aluminum nitrate solution, the treated aluminum nitrate and the anhydrous ethanol are mixed in a mass ratio of 1:10-15. In the preparation of the mixed polyvinyl alcohol solution, the polyvinyl alcohol 1788 aqueous solution and the Tween 80 are mixed in a mass ratio of 1000:2-3. In the preparation of the first mullite sol, the aluminum nitrate in the aluminum nitrate solution and the tetraethyl orthosilicate are mixed in a molar ratio of 3-3.2:
1. The molar concentration of the dilute nitric acid is 0.1-0.2 mol / L. The addition speed of the dilute nitric acid is 3-5 mL / min.
2. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by In the preparation of the second mullite sol, the tetraethyl orthosilicate and the anhydrous ethanol are mixed in a mass ratio of 13-15:50-55. The molar ratio of the tetraethyl orthosilicate to the aluminum isopropoxide is 1:2.6-2.
8. The molar ratio of the aluminum isopropoxide to the aluminum nitrate in the aluminum nitrate solution is 5.7-6:
1.
3. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by, 4. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by, 5. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by, 6. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by, 7. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by, The mass ratio of the first portion of mullite sol to the second portion of mullite sol is 10:2-2.4 in the mixing; The temperature of the vacuum concentration is 60-70 DEG C, and the vacuum degree is 0.02-0.05 MPa.
8. The boron nitride coating for high-temperature-resistant electric insulation according to claim 1, characterized by, The organic auxiliary agent is one or a combination of hydroxyethyl cellulose and carboxymethyl cellulose; The wetting agent is aqueous silicone oil; The dispersing agent is maleic acid-acrylic acid copolymer; The defoaming agent is polyether modified silicone defoaming agent.
9. A process for the production of the boron nitride coating for high temperature resistance and electrical insulation according to any one of claims 1 to 8, characterized in that, It comprises: Preparing raw materials, ball milling; The preparation of raw materials is to take each raw material according to the specified weight fraction; The ball milling is to mix and stir each raw material uniformly, then ball mill and sieve to obtain boron nitride coating for high temperature resistance, electrical insulation and the like.
10. The method of claim 9, wherein the boron nitride coating is prepared by a method comprising: preparing a boron nitride slurry by mixing a boron nitride powder and a solvent; and coating a surface of a substrate with the boron nitride slurry. The rotation speed of the ball mill in the ball milling is 200-400 rpm, and the ball milling time is 1-4 h; The mesh size of the screen used in the sieving is 200 mesh.
Citation Information
Patent Citations
Boron nitride coating and application method
CN103708843A
An anti-stick aluminum coating
CN107201066B
Boron nitride high-temperature-resistant anti-corrosive paint and preparation method thereof
CN108585634A